Dynamische Simulation der Mechanischen Flüssigkeitsabtrennung in Vollmantelzentrifugen - Gleiß, Marco (KIT Scientific Publishing, 2018)
The aim of the present work is the mathematical modeling of solid bowl centrifuges for the dynamic simulation of separation processes in real time. The developed compartment model couples the residence time behavior with the material properties and thus allows a time and space-resolved simulation for solid bowl centrifuges. The profound insights into the separation process open up not only a better design, but also new fields of application such as the dynamic flowchart simulation.